2017
DOI: 10.1080/20002297.2017.1322446
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for methicillin-resistant Staphylococcus aureus colonization among human immunodeficient virus–infected outpatients in Taiwan: oral Candida colonization as a comparator

Abstract: Human immuodeficency virus (HIV)-infected patients receiving highly active antiretroviral therapy (HAART) and community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) have increased in recent years in Taiwan. This study was undertaken to determine the prevalence of and risk factors for nasal and oral S. aureus and MRSA colonization among contemporary HIV-infected populations. Clinical variables for S. aureus and MRSA colonization among HIV-infected outpatients from three hospitals were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
0
15
2
Order By: Relevance
“…The nasal carriage rate of MRSA in this study is slightly lower than that previously reported in Taiwan in 2003 (5.6% of 296 HIV-infected patients) [12] and in 2009-2010 (4.4% of 457 HIV-infected patients) [23]. Compared with other populations in Taiwan, the nasal MRSA carriage rate among HIV-infected patients was significantly lower than that for patients hospitalized in the intensive care units (ICU) (32% of 177 patients) [30], but similar to that for adult patients receiving hemodialysis (3.8% of 296 patients) [31], adult patients visiting emergency room (3.8% of 502 patients) [32] and otherwise healthy adults for health examination (3.8% of 3098 adults) [33].…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The nasal carriage rate of MRSA in this study is slightly lower than that previously reported in Taiwan in 2003 (5.6% of 296 HIV-infected patients) [12] and in 2009-2010 (4.4% of 457 HIV-infected patients) [23]. Compared with other populations in Taiwan, the nasal MRSA carriage rate among HIV-infected patients was significantly lower than that for patients hospitalized in the intensive care units (ICU) (32% of 177 patients) [30], but similar to that for adult patients receiving hemodialysis (3.8% of 296 patients) [31], adult patients visiting emergency room (3.8% of 502 patients) [32] and otherwise healthy adults for health examination (3.8% of 3098 adults) [33].…”
Section: Discussioncontrasting
confidence: 79%
“…MRSA has been a prevalent etiology of infections in Asian countries, including Taiwan, either in healthcare settings or in the community, for decades, but the reports regarding MRSA colonization in HIV-infected population have been scarce [12,15,23]. Hence, we conducted this study to evaluate the prevalence of and associated factors for MRSA colonization in HIV-infected population in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…aureus . That the source of swabs used to determine prevalence of S. aureus influences the level of prevalence is attested to by the findings of other researchers [32,45]. These researchers recorded approximately 2–3-fold higher prevalence of S .…”
Section: Discussionmentioning
confidence: 92%
“…Among HAIs, polymicrobial infections are associated with severe clinical outcomes, frequently leading to aggressive infections. In most cases, polymicrobial infections exert an impact on therapeutic procedures and display increased clinical resistance to prescribed antibiotics [ 5 , 6 ]. Globally, the fungus Candida species and the Gram-positive bacterium Enterococcus species are ranked among the top microorganisms that frequently co-exist in polymicrobial infections [ 2 ].…”
Section: Introductionmentioning
confidence: 99%